Perancangan dan Pengembangan Video Review Sebagai Media Iklan Pada Website Marketplace Dengan Metode Research & Development - Heru Wijayanto Aripradono; Raudlatul Khairiah (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2022)
Promotion is an important activity in marketing. The success of marketing depends on how the promotion is carried out. An effective form of promotion has several elements: advertising, personal selling, sales promotion, and publicity. Promotion is an activity in marketing that has a level of success judged by how the promotion is done. This form of promotion has complete videos ranging from real visualizations, motion pictures, sound elements called multimedia. Video review is a marketing communication that can influence the decision process in purchasing. Braindo is an e-commerce marketplace that focuses on equipment for household needs. This design uses a research & development method where at the research stage, the author analyses the data from the questionnaire and interviews three married couples who obtained raw data in the form of a questionnaire. After that, the author designed a video review as an advertising medium at the development stage.